2015
DOI: 10.1016/j.jag.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

3D object-oriented image analysis in 3D geophysical modelling: Analysing the central part of the East African Rift System

Abstract: Non-uniqueness of satellite gravity interpretation has traditionally been reduced by using a priori information from seismic tomography models. This reduction in the non-uniqueness has been based on velocity-density conversion formulas or user interpretation of the 3D subsurface structures (objects) based on the seismic tomography models and then forward modelling these objects. However, this form of object-based approach has been done without a standardized methodology on how to extract the subsurface structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…This might be particularly useful for the inversion of potential field data where lateral variations are often reasonably well modelled but the depth resolution is very poor, thereby leaving a large degree of uncertainty on the final model in both object boundaries and property characteristics. A case study implementation for reducing non-uniqueness in satellite gravity inversions is shown by Fadel et al (2013). This also might be particularly relevant for recent satellite gravity studies which use seismic tomography models (for a review, see van der Meijde et al 2013b).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 96%
“…This might be particularly useful for the inversion of potential field data where lateral variations are often reasonably well modelled but the depth resolution is very poor, thereby leaving a large degree of uncertainty on the final model in both object boundaries and property characteristics. A case study implementation for reducing non-uniqueness in satellite gravity inversions is shown by Fadel et al (2013). This also might be particularly relevant for recent satellite gravity studies which use seismic tomography models (for a review, see van der Meijde et al 2013b).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 96%
“…However, using vote maps to extract features from a collection of seismic tomographies is the most basic way to do this, and a more refined method (e.g. Fadel et al, 2015) could lead to better constrained volumes. In particular it might benefit an inversion if uncertainties could be placed on the size and position of the volumetric features to allow them to change during inversion.…”
Section: Discussionmentioning
confidence: 99%
“…The regularization parameters β and γ exert critical control over the resulting density structure and the achievable data fit. The most popular methods to determine such parameters are L curves and cross-validation (Farquharson and Oldenburg, 2004). Here we use cross-validation to estimate the regularization parameter.…”
Section: Cross-validation Inversion Approachmentioning
confidence: 99%
“…For these models alternative analysis approaches might be more relevant. Recent developments use object oriented segmentation approaches for upper mantle seismic tomography models to obtain a priori information on subsurface tectonical objects (Fadel et al, 2014(Fadel et al, , 2015. With this approach no generic starting values (density, thickness) for the whole continent have to be selected (Tugume et al, 2013;van der Meijde et al, 2013a).…”
Section: The Way Forwardmentioning
confidence: 99%